Robot-assisted excision of partially obstructing ureteral fibroepithelial polyp in a child: A case report and review of the literature - Edoardo Bindi; Fabiano Nino; Taisia Bollettini; Elisa Chiarella; Giovanni Cobellis (Journal of Pediatric Surgery Case Reports, 2022)
Background: Fibroepithelial polyps are benign tumors located in the upper ureter and ureteropelvic junction. Given their location in rare cases they can cause hydronephrosis. Clinically and radiologically, it is difficult to distinguish them from ureteropelvic junction obstruction. Case report: A 6-years boy was admitted with intermittent left flank pain. An ultrasound revealed a III degree hydronephrosis, confirmed by an MR examination which highlighted an obstruction at the level of the middle tract of the ureter. We performed a robotic intervention. During surgery the presence of ureteral polyp was evident as the cause of the obstruction. An end-to-end uretero-ureteral anastomosis was performed. Conclusion: Ureteral polyps were mainly reported in adults, but recently several series revealed higher incidence among pediatric patients. Diagnosis of ureteral polyps is challenging, but even without a definite diagnosis, the best strategy is that of a robotic approach similar to that of the pathologies of the ureteropelvic junction.